Thanksgiving on Thursday - Osborne, Mary Pope.; Murdocca, Sal. (2003)
Jack and Annie travel to the year 1621, where they celebrate the first Thanksgiving with the Pilgrims and Wampanoag Indians in the New Plymouth Colony.
7-11
Keywords: Jack -- (Fictitious character from Osborne) -- Juvenile fiction; Annie -- (Fictitious character from Osborne) -- Juvenile fiction; Thanksgiving Day -- Juvenile fiction; Pilgrims (New Plymouth Colony) -- Juvenile fiction; Time travel -- Juvenile fiction; Plymouth (Mass.) -- History -- 17th century -- Juvenile fiction; Fiction